تقييم الخدمات العامة لمركز المجاورة السكنية غوط الشعال (Journal of Humanitarian and Applied Sciences, 2016)
Neighboring residential center of one of the pillars of planning aimed at providing a decent life for residents through the center includes all services and surrounded by all the cultural events, educational and religious, taking into account the spatial distribution of the terms of access for pedestrians and car users.Due to the importance of an integrated service centers according to planning standards study examined the availability of services adjacent to the center Got Alshall and knead through the neighboring and comparable generations planning schemes field survey as well as evaluating the available services as planning standards for the centers, residential neighborhoods Libyan The study concluded that a series of important results the availability of an integrated service center for the adjacent residential and in the light of these results has been proposed a number of recommendations aimed at developing neighborhoods schemes.